Epidemiology of Communicable and Non-Communicable Diseases Attributes of Lifestyle and Nature on Humankind - Kasenga, Fyson H. (IntechOpen, 2016)
Human sufferings, including deaths, can be reduced or avoided by applying routine principles of hygiene in individuals' lives. Some hygiene routines are purely simple remedies, which are inexpensive, affordable, acceptable and easily accessible. It is evident that change is first enacted from within the mindset of an individual, then transmitted to families, groups and communities, and eventually the mindset of a nation can change creating an environment which is better for everybody to live in. This book contains chapters discussing conditions or diseases that may not be common in the readers' area. Caution as such may never be underestimated considering the fact that we are living in a global village where one can never say 'this does not occur in my area' but rather question, does this occur in my community, why does it occur, who is affected, where and when does it occur and what can be done about it? These questions constitute what epidemiology is all about, and their precise and comprehensive answers can transform lives and help us have the right perceptions for the health challenges we face and accept the possibility of dealing with them directly.